Environmental, economic and social perceptions of community members on the role of water, soil and natural grasslands as a basis for local development in Acopalca, Peru - Maldonado Oré, Edith M.; Yaranga Cano, Raul Marino; Pizarro Carcausto, Samuel Edwin; Cano, Deyvis (Head Start Network for Education and Research, 2024)
The concept of ecosystem services has gained popularity among academics, researchers and policymakers to support environmental management and biodiversity conservation, so that many development projects in rural areas have merited investment for restoration and improvement of grassland ecosystems accompanied by training programs for the beneficiaries, With this criterion in mind, the study investigated the perception of puna pastoralists in Acopalca, Peru, regarding the degree of knowledge about the significance of the ecosystem services provided by soil-water-grasslands, with the objective of characterizing the environmental, social and economic dimensions of this local perception, through the application of a survey to the representative of the livestock family affiliated to two producers' associations. It was evidenced that cattle-raising families have a limited understanding of the role of the natural resources they directly access and little clarity on the relationship between natural pastures, family income and access to basic services. The results revealed limitations in environmental perception, evidencing a lack of knowledge about the multifaceted contribution of pastures. Social perception showed neutrality in the relationship between pastures and family income, and a discrepancy in access to basic services. The comparison between associations highlighted significant differences, indicating the need for training strategies adapted to the local idiosyncrasies of the beneficiaries. In conclusion, addressing the deficiencies identified in community understanding was essential to strengthening sustainable natural resource management in Acopalca. It highlights the importance of designing specific training programs, considering the particularities of each group, to promote self-management and community participation and thus achieve more comprehensive and sustainable local development.